A survey on nasoalveolar moulding treatment practices at cleft centres across India - Thiruvenkatachari, Badri; Vaidhyalingam, Thailavathy; Chakkaravarthi, Subhiksha; Prathap, Manoj; Nambiar, Karthika (Frontiers in Surgery, 2025)
BackgroundThe purpose of this study is to assess the current protocols followed in the practice of NAM treatment for patients with cleft lip and palate across different comprehensive centres in India.DesignCross sectional questionnaire based study.MethodComprehensive cleft teams across India were invited to participate in this survey. The questionnaire was developed over four stages, with a panel of eight members. The developed questionnaire consisted of 29 questions that included demographic details, decision-making process, treatment protocols, experiences with treating patients, difficulties and complications encountered during treatment. The results were reported descriptively in percentages.ResultsOf the 46 teams, 39 teams (85%) reported offering NAM before lip surgery, while 15% (n = 7) teams did not offer NAM. Of these 39 teams, almost half (49%, n = 19) of the teams were providing NAM to less than 20% of their patients, 28% (n = 11) of the teams were providing treatment to more than 50%, and the remaining respondents reported (23%, n = 9) providing NAM to 21%–50% of their patients. There is a consensus that NAM is beneficial for both unilateral and bilateral clefts, with the Grayson's method as the most commonly used technique. While there is general agreement on their effectiveness, 15% of participants were unsure. The most frequently reported side effects were cheek and mucosal irritation. Despite these issues, all respondents would recommend NAM treatment.ConclusionThe survey demonstrated a strong consensus among centers regarding most aspects of NAM treatment. Notably, all respondents expressed their willingness to recommend NAM to their friends and family.